MOLECULAR CHARACTERIZATION OF DOMINANT YEAST STRAINS ISOLATED DURING ETHANOL FERMENTATION PROCESS - Viana, NÃ¡dia Cristina; Defavari do Nascimento, Daniela; Prada, Marcos; da Cruz, Sandra Helena (REVISTA DE AGRICULTURA, 2020)
The Brazilian fermentation process has unique characteristics, such as the utilization of acid yeast cell recycling. The difficulty to sterilize large volumes of water and sugarcane juice enables the presence of indigenous yeasts. Occasionally, those yeast strains are better adapted and exert dominance over the commercial strains employed in the fermentation process. This study explored the prevalence of indigenous yeast strains in an ethanol producing unit in Brazil. The samples, ranging from beginning to late stages of the harvest season, show the presence of indigenous yeast. This can be observed by the divergence in PCR banding patterns from the samples, when compared to the commercial yeast strain PE-2 utilized by this particular ethanol producing unit. The results obtained point to the dominance of indigenous yeasts in the fermentation system that surpass in occurrence the commercial strain in all stages of the harvest season.